Enhanced growth and osteogenic differentiation of Induced Pluripotent Stem cells by Extremely Low-Frequency Electromagnetic Field - Ardeshirylajimi, A; Soleimani, M (Cellular and Molecular Biology, 2015)
It is accepted that induced pluripotent stem cells (iPSCs) have a great osteogenic potential differentiation, in the present study, we tried to improve this potentials using mechanical and biological stimulation. To achieve this goal, the influence of prolonged pulsed extremely low frequency electromagnetic field (ELF-EMF) (50 Hz and 1.5 mT) was investigated on cultured iPSCs. After evaluation of iPSCs biological behavior under radiation using MTT assay, osteogenic differentiation of stem cells was investigated via common important osteogenic markers such as alkaline phosphatase (ALP) activity, calcium mineral deposition and important bone-related genes. MTT result showed that proliferation rate of iPSCs significantly increased followed by stimulate with ELF-EMF. Osteogenic differentiation characterization demonstrated that potential of stem cells also was significantly increased while these cells cultured under both ELF-EMF and osteogenic medium (OM) in comparison to cultured under ELF-EMF or OM alone. According to the results, concluded that combination of OM and ELF-EMF can be a great supplement for bone differentiation of stem cells and appropriate candidate for use in the treatment of bone defects and osteoporosis patients by accelerating healing process.